TINDAK TUTUR EKSPRESI MARAH DALAM FILEM DEATH NOTE SEASON 1 (2015) - Andi Abd. Khaliq Syukur; Yanti Hidayati; Hafiyyan Irham Sukmana (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2022)
This study aims to describe angry expressive speech acts and angry expressive speech act patterns in the film Death Note Season 1 (2015). Leech’s (1993) theory of pragmatics, Austin’s (1962) theory of speech acts, Searle’s (1969) theory of angry expression, and Yule’s (2014) theory of angry expression speech act were used in this study. This research was conducted by identifying the speech acts of angry expressions. The data that has been identified was analyzed using a qualitative descriptive method. The identification results contained 22 data of angry expressive speech acts. The analysis shows that the expressive speech act of anger is influenced by the context in the film. In addition, the pattern of expressive speech acts displayed has three tendencies. First, the meaning conveyed with the illocutionary has another meaning from the speaker. Second, utterances have direct and indirect meanings. Third, the utterance has a marker of angry expression but the speaker does not mean to be angry.